Theoretical Foundations For The Development Of Professional Training Of Future Engineers On The Basis Of Digital Technologies - Tursunov Muzaffar Ilkhomovich (Genius Journals, 2024)
This article aims to set the priorities for the development of the educational process based on the use of digital technologies in the higher education system of the Republic, the analysis of their capabilities, digital technologies in the field of education and in what form they were introduced.
Keywords: Digital technologies; information and communication; technologies; higher education system